Education as a factor of cognitive society development in the conditions of digital transformation - Nikitenko, Vitalina; Voronkova, Valentyna; Oleksenko, Roman; Andriukaitiene, Regina; Holovii, Liudmyla (Journal of the University of Zulia, 2022)
The purpose of the study is to conceptualize the cognitive development of society as a factor of digital transformation. The solution of this problem contributes to the formation of a new theory that requires the introduction of innovative technologies that play a very important role in the sustainable development of society. The research methodology used consists of axiological, comparative, synergistic, structural-functional methods and approaches. The emergence of a new "digital person" is explored, whose essence is that the technological revolution has made it possible for everyone to connect to the network, to contribute to the network effect, allowing people to work in real time and generate income by moving in the markets. The concept of the formation of the digital economy has been structured, as a factor in the cognitive development of society, and new digital strategies have been revealed for firms, companies, organizations, companies that face immeasurable challenges and opportunities for digitization and for achieve success.